Lagrangian measurements of incipient motion in oscillatory flows. Issue 1 (21st January 2015) - Frank, Donya; Foster, Diane; Sou, In Mei; Calantoni, Joseph; Chou, Pai
Abstract Incipient motion of coarse gravel‐sized sediment was investigated under a range of oscillatory flows. This article examines the relative significance of shear stresses and pressure gradients in triggering motion, which was directly measured with electronic Smart Sediment Grains (SSGs). The data suggest that incipient motion was induced by the pressure gradients in flows with large accelerations, by the shear stresses in flows with low accelerations and greater shear, and by the combined effects in intermediate flows. A modified incipient motion criterion was evaluated accounting for the combined effects of the shear stresses and pressure gradients, which may be more widely applicable in the marine environment.